A Numerical study for inward solidification of a liquid contained in cylindrical and spherical vessel - Rajeev; Das S. (My University, 2025)
This study presents a numerical solution of inward solidification of phase change material contained in cylinder/sphere. Here, constant thermal property is assumed throughout the analysis for the liquid, which is initially at fusion temperature. The governing dimensionless equations of the above problem and boundary conditions are converted to initial value problem of vector matrix form. The time function is approximated by Chebyshev series and the operational matrix of integration is applied. The solution is utilized iteratively in the interface condition to determine the time taken to attain a fixed interface position.